Enhancing Collaboration and Learning Through a Problem-Based Game in Lower Secondary Social Studies - Amalina Farida; Sriyanto Sriyanto; Seyithan Demirdag (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
This study was motivated by the low collaboration skills and learning outcomes in social studies subjects, which are attributed to monotonous learning methods and the underutilization of digital learning media. The research aims to analyze the effectiveness of the